State strategies of governance in biomedical innovation: aligning conceptual approaches for understanding 'Rising Powers' in the global context - Faulkner Alex; Salter Brian (BMC, 2011)
Abstract Background 'Innovation' has become a policy focus in its own right in many states as they compete to position themselves in the emerging knowledge economies. Innovation in biomedicine is a global enterprise in which 'Rising Power' states figure prominently, and which undoubtedly will re-shape health systems and health economies globally. Scientific and technological innovation processes and policies raise difficult issues in the domains of science/technology, civil society, and the economic and healthcare marketplace. The production of knowledge in these fields is complex, uncertain, inter-disciplinary and inter-institutional, and subject to a continuing political struggle for advantage. As part of this struggle, a wide variety of issues - regulation, intellectual property, ethics, scientific boundaries, healthcare market formation - are raised and policy agendas negotiated. Methods A range of social science disciplines and approaches have conceptualised such innovation processes. Against a background of concepts such as the competition state and the developmental state, and national innovation systems, we give an overview of a range of approaches that have potential for advancing understanding of governance of global life science and biomedical innovation, with special reference to the 'Rising Powers', in order to examine convergences and divergences between them. Conceptual approaches that we focus on include those drawn from political science/political economy, sociology of technology; Innovation Studies and Science & Technology Studies. The paper is part of a project supported by the UK ESRC's Rising Powers programme. Results We show convergences and complementarities between the approaches discussed, and argue that the role of the national state itself has become relatively neglected in much of the relevant theorising. Conclusions We conclude that an approach is required that enables innovation and governance to be seen as 'co-producing' each other in a multi-level, global ecology of innovation, taking account of the particular, differing characteristics of different emerging scientific fields and technologies. We suggest key points to take account of in order in the future to move toward a satisfactory integrative conceptual framework, capable of better understanding the processes of the emergence, state steerage and transnational governance of innovative biomedical sectors in the Rising Powers and global context.